Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0023736
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modifications in Plant Disease Resistance

Abstract: Under constant attack from an ever‐evolving array of pathogens, the multilayered plant immune system provides a broad‐spectrum resistance that is the result of millions of years of coevolution of plants and microorganisms. Driving the arms race for survival is the continual diversification of defence and attack mechanisms. This process can be rapidly and efficiently achieved by posttranslational modifications (PTMs). Phosphorylation and ubiquitination are important PTMs involved in plant immune signalling that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Many key transcriptional regulators including DREB2, ICE1 (controlling cold, heat, salt, and drought stress), NPR1 (regulator of salicylic acid responses), and ABI5 (regulator of abscisic acid responses) have been shown to undergo these PTMs in order to be effective in promoting plant stress adaptation ( Miura et al , 2009 ; Miura and Hasegawa, 2010 ; Saleh et al , 2015 ), and PTMs have also been shown to be influential in countering biotic stresses ( Casey et al , 2017 ). PTMs are also relevant to agronomically important alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Many key transcriptional regulators including DREB2, ICE1 (controlling cold, heat, salt, and drought stress), NPR1 (regulator of salicylic acid responses), and ABI5 (regulator of abscisic acid responses) have been shown to undergo these PTMs in order to be effective in promoting plant stress adaptation ( Miura et al , 2009 ; Miura and Hasegawa, 2010 ; Saleh et al , 2015 ), and PTMs have also been shown to be influential in countering biotic stresses ( Casey et al , 2017 ). PTMs are also relevant to agronomically important alleles.…”
Section: Introductionmentioning
confidence: 99%